2012
DOI: 10.1111/j.1538-7836.2012.04773.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombophilias and adverse pregnancy outcomes: results from the Danish National Birth Cohort

Abstract: Summary.  Background:  Inherited thrombophilias have inconsistently been linked to adverse pregnancy outcomes. Differences in study design, size and population could explain this heterogeneity. Objective:  The aim of the present study was to evaluate if factor (F)V Leiden G1691A, prothrombin mutation G20210A (PTM) and methylenetetrahydrofolate reductase C677T (MTHFR) increased the risk of severe preeclampsia, fetal growth restriction, very preterm delivery, placental abruption and a composite of these outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 41 publications
(46 reference statements)
0
57
0
5
Order By: Relevance
“…MTHFR 677T was associated with placental infarcts and subsequent fetal growth restriction (Hefler et al, 2004;Lin and August, 2005). In the study from Lykke et al (2012), MTHFR C677T was significantly associated only with severe preeclampsia (OR = 1.3). Nair et al (2012) reported strong association of this polymorphism with recurrent pregnancy loss in the population from northern India.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…MTHFR 677T was associated with placental infarcts and subsequent fetal growth restriction (Hefler et al, 2004;Lin and August, 2005). In the study from Lykke et al (2012), MTHFR C677T was significantly associated only with severe preeclampsia (OR = 1.3). Nair et al (2012) reported strong association of this polymorphism with recurrent pregnancy loss in the population from northern India.…”
Section: Resultsmentioning
confidence: 94%
“…However, Subrt et al (2008) did not confirm the association of factor V Leiden with recurrent pregnancy loss in Czech patients. An extensive association study (Lykke et al, 2012) found out that factor V Leiden increased the risk of severe preeclampsia (OR = 1.6), fetal growth restriction (OR = 1.4), and placental abruption (OR = 1.7). Several studies dealing with pregnancy loss and thrombophilia were summarized in meta-analyses (Rey et al, 2003;Dudding and Attia, 2004), which describe the increased level of risk with OR ‡ 2 for carriers of factor V Leiden.…”
Section: Resultsmentioning
confidence: 99%
“…Preterm delivery (<37 weeks of gestation) accounts for 6 to 12% of deliveries in the developed world (Beck et al, ). The hazard ratios for CVD associated with total preterm delivery are on the order of 1.3 to 2.6 when compared with term births (Irgens et al, ; Smith et al, ; Pell et al, ; Wikstrom et al, ; Nardi et al, ; Catov et al, ; Lykke et al, ,b, ,b,c; Bonamy et al, ; Rich‐Edwards et al, ).…”
Section: Maternal Health Consequences Of Pregnancy Complicationsmentioning
confidence: 99%
“…Thrombotic risk factors have been associated with pregnancy complications [48]. Many previous studies have found an association between inherited thrombophilia and adverse pregnancy outcomes, however there has been wide variability in the strength of the association and some studies have not found a relationship [4,612].…”
Section: Introductionmentioning
confidence: 99%